Fenomena Bullying yang Dilakukan oleh Anak dalam Perspektif Sosiologi Hukum - Munajah, Munajah (Sharia Journal and Education Center Publishing, 2026)
The phenomenon of bullying by children shows an increasing and alarming rate. This article aims to analyze bullying by children as a social phenomenon related to legislation on child protection, as well as public perceptions based on prevailing norms. Through this analysis, the author finds that the high rate of bullying by children is caused by specific factors, particularly social media content that contains violence. Furthermore, weak education and laws that do not provide sanctions or deterrent measures for perpetrators also contribute to this problem. Therefore, it is necessary to review laws related to child protection and reform all forms of content that influence children's behavior in the form of bullying.